Oxygen generating biomaterials at the forefront of regenerative medicine: advances in bone regeneration - Zhao, Jiayi; Zhou, Chao; Xiao, Yang; Zhang, Kunyan; Zhang, Qiang; Xia, Linying; Jiang, Bo; Jiang, Chanyi; Ming, Wenyi; Zhang, Hengjian; Long, Hengguo; Liang, Wenqing (Frontiers in Bioengineering and Biotechnology, 2024)
Globally, an annual count of more than two million bone transplants is conducted, with conventional treatments, including metallic implants and bone grafts, exhibiting certain limitations. In recent years, there have been significant advancements in the field of bone regeneration. Oxygen tension regulates cellular behavior, which in turn affects tissue regeneration through metabolic programming. Biomaterials with oxygen release capabilities enhance therapeutic effectiveness and reduce tissue damage from hypoxia. However, precise control over oxygen release is a significant technical challenge, despite its potential to support cellular viability and differentiation. The matrices often used to repair large-size bone defects do not supply enough oxygen to the stem cells being used in the regeneration process. Hypoxiainduced necrosis primarily occurs in the central regions of large matrices due to inadequate provision of oxygen and nutrients by the surrounding vasculature of the host tissues. Oxygen generating biomaterials (OGBs) are becoming increasingly significant in enhancing our capacity to facilitate the bone regeneration, thereby addressing the challenges posed by hypoxia or inadequate vascularization. Herein, we discussed the key role of oxygen in bone regeneration, various oxygen source materials and their mechanism of oxygen release, the fabrication techniques employed for oxygen-releasing matrices, and novel emerging approaches for oxygen delivery that hold promise for their potential application in the field of bone regeneration.